Wayang civilizes religion: From spectacle to guidance - Rumbay, C.A.; Siahaya, J.; Hutagalung, S. (Acta Theologica, 2024)
Indonesia’s cultural acculturation and Christianity left behind by Islam are undeniable social realities that could be harmonised through puppetry. However, the propagator of Islam has used wayang (puppet) as a national symbol and original face. It has raised a polemic that involved serious conversations and sharp debates between religious and customary communities and invited the struggle of religious-cultural groups. Efforts to acculturate Christianity and culture in Java have not received serious attention. However, various opportunities could be used as media or objects of encounter such as wayang. Christian inculturation with a wayang perspective could contribute to the contextualisation of mission in Java, promoting smooth conversations with the community. This study aims to capture the potential that contributes to wayang for the mission and contextualisation of Christianity. A qualitative method with an analytical-descriptive approach was used to examine the past mission of Islam as well as wayang and model contextualisation in church traditions. The findings show that wayang is an opportunity for Christianity to take root and grow together with its culture. It must be an aim in the contextualisation mission to civilise Christianity in society.